Aziridine modified polyphenylene ether, preparation method and application thereof

By introducing aziridine functional groups into polyphenylene ether, a simple two-step reaction method is adopted to solve the problem of harsh cross-linking reaction conditions and insufficient solvent resistance under high temperature conditions, and its thermosetting and chemical resistance are improved , suitable for high-frequency and high-speed electronic applications.

CN117510834BActive Publication Date: 2024-12-24GUANGDONG LONGYU NEW MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311249811.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2024-12-24
Estimated Expiration
2043-09-26

AI Technical Summary

Technical Problem

The existing polyphenylene ethers have harsh cross-linking reaction conditions under high temperature conditions and insufficient reaction activity, resulting in low cross-linking density and residual unreacted groups affecting the performance of cured resins. Its solvent resistance and chemical resistance are insufficient, making it difficult to meet high frequency The demand for high-speed electronic applications.

Method used

By introducing aziridine functional groups, a simple and gentle two-step reaction method is adopted. First, acrylic chloride and acid-applied acid agent are reacted in anhydrous solvent, and then reacted with aziridine to form highly reactive aziridine. Modified polyphenylene ether to improve its high temperature and chemical resistance.

Benefits of technology

The thermosetting transformation of polyphenylene ether is achieved, the glass transition temperature, thermal decomposition temperature and low water absorption rate are improved, the dielectric constant and dielectric loss are reduced, and its compatibility with epoxy resin is enhanced. It is suitable for copper clad plates. manufacture.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117510834B_ABST
    Figure CN117510834B_ABST
Patent Text Reader

Abstract

The invention discloses a kind of aziridine modified polyphenylene ether, preparation method and application thereof; Belong to the technical field of polyphenylene ether resin; Aziridine modified polyphenylene ether resin, the terminal end group of its polymer main chain is aziridine strained ring structure; Its preparation method comprises the following steps: (1) polyphenylene ether is dissolved in anhydrous solvent, an acid dressing is added, acryloyl chloride is added dropwise at 0-5°C, and after the addition is complete, room temperature stirring is restored for 8-12 hours; After the reaction is completed, the solvent is removed, the by-product is washed and removed, and the mixture is precipitated in a mixed solvent of methanol and water, and then solid-liquid separation is performed, and finally dried to obtain a modified polyphenylene ether having an end group of acrylate functional group; (2) the modified polyphenylene ether having an end group of acrylate functional group is added in anhydrous solvent, excess aziridine is added, stirred at room temperature for 15-20 hours, and the solvent is drained to obtain an aziridine modified polyphenylene ether resin. The present invention aims to provide an aziridine modified polyphenylene ether having a simple preparation method, relatively mild conditions and good effects; It is used for copper clad laminate preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polyphenylene ether, more specifically, to an aziridine-modified polyphenylene ether and also relates to a preparation method and application thereof. Background Art

[0002] Polyphenylene oxide (PPO) is widely used in the preparation of high-frequency substrates due to its low water absorption, low dielectric constant, minimized dielectric loss, excellent heat resistance and outstanding processability. As the information technology revolution has entered a stage of high-speed signal transmission and high-frequency requirements in recent years, it is increasingly important to modify polyphenylene oxide to adjust its properties and adapt to specific electronic application requirements.

[0003] As a thermoplastic resin, polyphenylene ether has the disadvantages of high melting point, general processing performance, and poor solvent resistance. At present, the modification of polyphenylene ether mainly focuses on the following aspects: 1) Improving heat resistance: By introducing high temperature stabilizers or fillers, the high temperature resistance of polyphenylene ether can be enhanced, so that it can maintain stability during the manufacturing and use of circuit boards. 2) Enhancing mechanical properties: Adding reinforcing fillers such as glass fiber and carbon fiber can improve the strength, stiffness and wear resistance of polyphenylene ether to meet the mechanical requirements of circuit boards. 3) Improving flame retardant properties: Introducing flame retardants, nitrogen and phosphorus compounds, etc. can increase the flame retardant properties of polyphenylene ether, reduce its flammability, and improve the safety of circuit boards. 4) Improving chemical resistance: By adding chemical resistant fillers or chemical stabilizers, the chemical resistance of polyphenylene ether can be enhanced, so that it can resist chemical corrosion and environmental influences. 5) Adjusting processing properties: Selecting a suitable chemical modification method can adjust the melt fluidity and processing properties of polyphenylene ether to meet the needs of the copper clad laminate manufacturing process.

[0004] Post-polymerization modification of the chemical structure of polyphenylene ether, such as chemical modification of the terminal phenolic hydroxyl group of polyphenylene ether, introduction of functional groups such as C=C double bond (CN104072751A, CN102993683), amino group (CN106916293B), maleimide (CN103102484B), and silicone (CN106916293), is conducive to obtaining modified polyphenylene ether with good mechanical properties and excellent dielectric properties, and is becoming the preferred resin material for high-frequency and high-speed substrate materials. Among these introduced terminal functional groups, olefins (SABIC, NORYL TMSA9000), maleimide and other groups can undergo cross-linking reactions under high temperature and other conditions, turning thermoplastic polyphenylene ether into thermosetting resin, improving the solvent resistance of polyphenylene ether resin, compatibility with epoxy resin and the process performance of preparing copper clad laminates. However, the cross-linking conditions of these groups are relatively harsh, requiring the use of free radical initiators under high temperature conditions, or insufficient reaction activity resulting in low cross-linking density, and the residual unreacted groups affect the various properties of the cured resin.

[0005] Aziridine is a high-tension three-membered cyclic compound. This type of crosslinking agent has a wide range of uses, such as improving the water resistance, washing resistance, chemical resistance and high temperature resistance of leather coatings; improving the water resistance, anti-stickiness and high temperature resistance of water-based printing coatings; improving the water resistance and detergent resistance of inks; and improving the water resistance, alcohol resistance, detergent resistance, chemical resistance and wear resistance of parquet floor paint. Therefore, the aziridine functional group helps to improve adhesion, high temperature resistance, etc. The study of introducing aziridine groups into polyphenylene ether resins has a positive effect on improving the performance of polyphenylene ether. Summary of the invention

[0006] The first object of the present invention is to provide an aziridine-modified polyphenylene ether with a simple preparation method, relatively mild conditions and good effect in view of the above-mentioned deficiencies in the prior art.

[0007] The second object of the present invention is to provide a method for preparing the aziridine-modified polyphenylene ether.

[0008] The third object of the present invention is to provide an application of the above-mentioned aziridine-modified polyphenylene ether.

[0009] The first technical solution of the present invention is achieved as follows: an aziridine-modified polyphenylene ether resin, the terminal end group of the polymer main chain of which is an aziridine strained ring structure.

[0010] In the above-mentioned aziridine-modified polyphenylene ether resin, the chemical structure of the aziridine-modified polyphenylene ether is as follows:

[0011]

[0012] Wherein, R represents a methyl group or a hydrogen atom; n is an independent integer related to the number average molecular weight of the polyphenylene ether. The number average molecular weight of the polyphenylene ether is not particularly limited, preferably 1000-6000, and the corresponding n is 8-50.

[0013] The second technical solution of the present invention is achieved as follows: a method for preparing the above-mentioned aziridine-modified polyphenylene ether resin, the method comprising the following steps:

[0014] (1) Dissolve polyphenylene ether in an anhydrous solvent, add an acid dressing agent, and dropwise add acryloyl chloride at 0-5°C. After the dropwise addition is complete, return to room temperature and stir for 8-12 hours;

[0015] After the reaction is completed, the solvent is removed by distillation under reduced pressure, triethylamine hydrochloride or pyridine hydrochloride byproducts are removed by washing with water, and then precipitated in a mixed solvent of methanol and water, followed by solid-liquid separation, and finally dried in a vacuum environment at 40° C. to obtain a modified polyphenylene ether having an acrylate functional group as the terminal group;

[0016] (2) Modified polyphenylene ether with terminal acrylate functional group: Add excess aziridine to an anhydrous solvent, stir at room temperature for 15-20 hours, and drain the solvent to obtain aziridine-modified polyphenylene ether resin.

[0017] In the above-mentioned method for preparing an aziridine-modified polyphenylene ether resin, in step (1) or (2), the anhydrous solvent is tetrahydrofuran or dichloromethane.

[0018] In the above-mentioned method for preparing an aziridine-modified polyphenylene ether resin, in step (1), the acid coating agent is any one of triethylamine, pyridine and diisopropylethylamine.

[0019] In the above-mentioned method for preparing an aziridine-modified polyphenylene ether resin, in step (1), the molar ratio of the polyphenylene ether, acryloyl chloride and acid-coating agent is 1:4-8:2-6.

[0020] In the above-mentioned method for preparing an aziridine-modified polyphenylene ether resin, in step (2), the molar ratio of the modified polyphenylene ether to aziridine is 1:5-10.

[0021] The third solution of the present invention is achieved as follows: an application of an aziridine-modified polyphenylene ether resin in the preparation of a copper-clad laminate. Preferably, the aziridine-modified polyphenylene ether is blended with one or more of an epoxy resin, a hydrocarbon resin or a cyanate resin, and the copper-clad laminate is obtained after curing.

[0022] Compared with other types of modified polyphenylene ether resins that have been invented, the present invention has the following beneficial effects:

[0023] The present invention creatively introduces highly reactive aziridine functional groups into the end groups of polyphenylene ether, so that the polyphenylene ether has relatively excellent epoxy compatibility, and is transformed from a thermoplastic resin to a thermosetting resin. The glass transition temperature of the polyphenylene ether is as high as 172 degrees, the thermal decomposition temperature (5% mass loss) is as high as 385 degrees, the water absorption rate is as low as 0.04%, and the dielectric constant and dielectric loss are both low.

[0024] The modified polyphenylene ether is prepared by two-step reaction, the preparation method is simple, the conditions are relatively mild, the reaction yield is high, no side reaction occurs, it is easy to separate and purify, the reaction economy is high, and it is suitable for large-scale production. The copper clad laminate prepared by aziridine-modified polyphenylene ether has great advantages, including low water absorption (as low as 0.17%), dielectric constant as low as 3.56 (10GHz), dielectric loss as low as 0.0037, and has great application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The present invention will be further described in detail below in conjunction with the embodiments in the accompanying drawings, but this does not constitute any limitation to the present invention.

[0026] Figure 1 It is a schematic diagram of the preparation route of the aziridine-modified polyphenylene ether of the present invention. DETAILED DESCRIPTION

[0027] See also Figure 1 As shown, the aziridine-modified polyphenylene ether resin of the present invention has an aziridine strained ring structure at the end of the polymer main chain. The structure has high reactivity, helps to improve the reactivity of the curing reaction, and improves the chemical resistance of the substrate.

[0028] The aziridine-modified polyphenylene ether resin is a powdered thermosetting resin at room temperature. The two ends of its main chain are aziridine (aziridine) with a three-membered strained ring structure. Under the condition of a curing agent, it can participate in ring-opening polymerization and curing to obtain a thermosetting resin with low water absorption and high temperature resistance.

[0029] The aziridine-modified polyphenylene ether has good compatibility with epoxy resin. Aziridine and epoxy both belong to ternary strained rings and can undergo ring-opening copolymerization in the presence of a curing agent, thereby increasing the crosslinking density after curing and the glass transition temperature of the copper-clad laminate substrate. Compared with modified polyphenylene ether with olefin as the terminal group, the aziridine-modified polyphenylene ether has a lower crosslinking temperature, and the heat resistance and interlayer adhesion of the substrate are better.

[0030] Preferably, the chemical structure of the aziridine-modified polyphenylene ether is as follows:

[0031]

[0032] Wherein, R represents a methyl group or a hydrogen atom; n is an independent integer related to the number average molecular weight of the polyphenylene ether. The number average molecular weight of the polyphenylene ether is not particularly limited, preferably 1000-6000, and the corresponding n is 8-50.

[0033] The terminal group of the modified polyphenylene ether is an aziridine strained ring structure with high reactivity. It can undergo ring-opening reactions with many types of compounds such as phenol, carboxylic acid, amine, alcohol, etc. under mild conditions to convert thermoplastic polyphenylene ether into thermosetting polyphenylene ether resin. This type of polyphenylene ether has good compatibility with epoxy resin. The cured substrate has a high glass transition temperature, thermal decomposition temperature, low water absorption, dielectric constant and dielectric loss, and is suitable for use as a copper clad laminate substrate.

[0034] The present invention provides a method for preparing the above-mentioned aziridine-modified polyphenylene ether resin, which comprises the following steps:

[0035] (1) Polyphenylene ether is dissolved in an anhydrous solvent, an acid dressing agent is added, and acryloyl chloride is added dropwise at 0-5°C. After the addition is completed, the mixture is returned to room temperature and stirred for 8-12 hours; the anhydrous solvent is tetrahydrofuran or dichloromethane; the acid dressing agent is any one of triethylamine, pyridine and diisopropylethylamine. The molar ratio of the polyphenylene ether, acryloyl chloride and the acid dressing agent is 1:4-8:2-6.

[0036] After the reaction is completed, the solvent is removed by distillation under reduced pressure, the by-product of triethylamine hydrochloride or pyridine hydrochloride is removed by washing with water, and then precipitated in a mixed solvent of methanol and water, followed by solid-liquid separation, and finally dried in a vacuum environment at 40° C. to obtain a modified polyphenylene ether with an acrylate functional group as the terminal group.

[0037] (2) Adding an excess of aziridine to a modified polyphenylene ether having an acrylate functional group as the terminal group in an anhydrous solvent, stirring at room temperature for 15-20 hours, and draining the solvent to obtain an aziridine-modified polyphenylene ether resin. The anhydrous solvent is tetrahydrofuran or dichloromethane; the molar ratio of the modified polyphenylene ether to aziridine is 1:5-10.

[0038] The invention discloses an application of an aziridine-modified polyphenylene ether resin in the preparation of a copper-clad laminate. Specifically, the aziridine-modified polyphenylene ether is blended with one or more of an epoxy resin, a hydrocarbon resin or a cyanate resin, and the copper-clad laminate is obtained after curing. The copper-clad laminate has a low dielectric constant and dielectric loss, a low water absorption rate and a high glass transition temperature.

[0039] Example 1

[0040] This embodiment provides an aziridine-modified polyphenylene ether, and the structure of the aziridine-modified polyphenylene ether is as follows:

[0041]

[0042] Wherein n is an integer from 8 to 50.

[0043] This embodiment also provides a method for preparing aziridine-modified polyphenylene ether, the preparation method comprising the following steps:

[0044] (1) Dissolve 100g of polyphenylene ether (number average molecular weight 1800, containing about 0.055mol of terminal phenol functional groups) in 500mL of dichloromethane, add triethylamine acidifier (0.15mol, 23.1mL), cool and stir in an ice-water bath, add acryloyl chloride (0.275mol, 22.5mL) dropwise with a dropping funnel, return to room temperature and stir for 12h after the addition, and a white precipitate is generated. Concentrate the reaction solution to about 200mL, precipitate it into 1L of a mixed solvent of methanol and water (volume ratio 1:1), separate the solid and liquid, collect the solid by suction, wash it with water and methanol in turn, and dry it at 40 degrees in a vacuum to obtain a modified polyphenylene ether with an acrylic acid end group, the structure of which is shown below:

[0045]

[0046] (2) Place a magnetic stirrer of suitable size in a 500mL round-bottom flask, add 60mL of deionized water, then add DL-aminopropanol (75g, 1mol), mix the mixture thoroughly and cool it to 0°C while stirring. Then dilute concentrated sulfuric acid (110g) to 1g / mL, and then drop the diluted sulfuric acid into the mixture solution. After stirring for 2 hours, heat the mixture under vacuum to remove water, then dissolve sodium hydroxide (100g, 2.5mol) in 200mL of water, drop the sodium hydroxide solution into the drained mixture solid, slowly heat until the solid is dissolved, stir at room temperature for 2 hours, and then distill at atmospheric pressure to obtain a crude product, and finally remove water from the sodium hydroxide solid to obtain a colorless and transparent liquid product (20.4g, 53% yield). The structure of the prepared 2-methylaziridine is as follows:

[0047]

[0048] 3) 50 g of polyphenylene ether (0.027 mol) with acrylate as the terminal group was dissolved in 200 mL of tetrahydrofuran, and 15 g of the prepared 2-methylaziridine (0.263 mol) was added under stirring, and stirred at room temperature for 20 hours. After the reaction was completed, the reaction solution was poured into 1 L of methanol, and the precipitated solid was collected by suction filtration and placed in a vacuum drying oven at 40 degrees to obtain a polyphenylene ether modified with terminal 2-methylaziridine.

[0049] The characterization data of hydrogen nuclear magnetic resonance spectrum are as follows: 1H NMR (400 MHz, CDCl3): δ 2.14 (s, 6H), 6.5 (s, 2H).

[0050] The molecular weight, glass transition temperature, thermal decomposition temperature, water absorption, dielectric constant and dielectric loss of the aziridine-modified polyphenylene ether prepared in this example were tested. The testing method is as follows:

[0051] Molecular weight determination: by gel permeation chromatography (SEC) test, with tetrahydrofuran as mobile phase and polystyrene as standard.

[0052] Glass transition temperature: tested by differential scanning calorimeter (DSC), where the temperature rise and fall rate during the test is 10

[0053] ℃ / min, first heat up and then cool down to eliminate the thermal history, and then do a second temperature increase measurement.

[0054] Thermal decomposition temperature: tested by thermogravimetric analyzer (TG). The testing process was carried out under nitrogen protection with a heating rate of 10°C / min.

[0055] Water absorption rate: hot press the modified polyphenylene ether into a solidified block of 10×5×15mm, weigh the solidified block with an analytical balance, and then soak it in distilled water at 25°C for 24 hours, take it out, wipe off the moisture on the surface of the solidified block, and weigh the weight of the solidified block after soaking with an analytical balance, and calculate it in %.

[0056] Dielectric constant and dielectric loss: The object to be tested was dissolved in tetrahydrofuran to form a 20% mass fraction solution, coated on a glass slide with a thickness of 300 μm, and dried at 80°C for 2 hours to obtain a dry film of about 25 μm thickness. The dielectric constant and dielectric loss of the obtained dry film were then tested by the cavity resonance method at a test frequency of 10 GHz.

[0057] The relative molecular weight of the 2-methylaziridine-modified polyphenylene ether prepared in this example is 2300, the glass transition temperature is 162 degrees, the thermal decomposition temperature is 371 degrees, the water absorption rate is as low as 0.06%, the dielectric constant is 3.50, and the dielectric loss is 0.0045.

[0058] This embodiment also uses the modified polyphenylene ether for copper clad laminate substrates.

[0059] The preparation method of the copper clad laminate is as follows: 50g of the above-mentioned 2-methylaziridine-modified polyphenylene ether, 50g of FR4 epoxy resin and 0.5g of resin curing agent for copper foil substrate are placed in 50mL of acetone, stirred and dissolved at room temperature, coated with 0.25mm, dried at 100 degrees, placed in a vacuum drying oven at 170 degrees for curing for 3 hours, cooled and demolded to obtain a 25um thick dry film, and then the dry film and copper foil are hot-pressed to obtain a copper clad laminate.

[0060] The water absorption rate, dielectric constant and dielectric loss of the obtained copper clad laminate were tested, and the test results showed that the water absorption rate, dielectric constant and dielectric loss of the copper clad laminate were 0.32%, 3.54 and 0.0039, respectively.

[0061] Example 2

[0062] This embodiment provides an aziridine-modified polyphenylene ether, and the structure of the aziridine-modified polyphenylene ether is as follows:

[0063]

[0064] (1) Dissolve 100g of polyphenylene ether (number average molecular weight 1800, containing about 0.11mol of terminal phenol functional groups) in 500mL of dichloromethane, add triethylamine acidifier (0.15mol, 21mL), cool and stir in an ice-water bath, add acryloyl chloride (0.22mol, 18mL) dropwise with a dropping funnel, return to room temperature and stir for 12h after the addition, and a white precipitate is generated. Concentrate the reaction solution to about 200mL, precipitate it into 1L of a mixed solvent of methanol and water (volume ratio 1:1), separate the solid and liquid, collect the solid by suction filtration, wash it with water and methanol in turn, and dry it in a vacuum at 40 degrees to obtain a modified polyphenylene ether with an acrylic acid end group, the structure of which is shown below:

[0065]

[0066] (2) Place a magnetic stirrer of appropriate size in a 500mL round-bottom flask, add 60mL of deionized water, then add ethanolamine (61g, 1mol), mix the mixture thoroughly and cool it to 0°C while stirring. Then dilute concentrated sulfuric acid (110g) to 1g / mL, and then drop the diluted sulfuric acid into the mixture solution. After stirring for 2 hours, heat the mixture under vacuum to remove water, then dissolve sodium hydroxide (100g, 2.5mol) in 200mL of water, drop the sodium hydroxide solution into the drained mixture solid, slowly heat until the solid is dissolved, stir at room temperature for 2 hours, and then distill at atmospheric pressure to obtain a crude product, and finally remove water from the sodium hydroxide solid to obtain a colorless and transparent liquid product (26g, 60% yield). The structure of the prepared aziridine is as follows:

[0067]

[0068] 3) 50 g of polyphenylene ether with acrylate as terminal group was dissolved in 200 mL of tetrahydrofuran, 12 g of prepared aziridine was added under stirring, and stirred at room temperature for 20 hours. After the reaction was completed, the reaction solution was poured into 1 L of methanol, the precipitated solid was collected by suction filtration, and placed in a vacuum drying oven at 40 degrees to obtain a polyphenylene ether modified with terminal aziridine.

[0069] The end-group modified polyphenylene ether prepared in this embodiment was tested in the same way as in Example 1, i.e., the amino-modified polyphenylene ether prepared in this embodiment had a molecular weight of 2200, a glass transition temperature of 158°C, a thermal decomposition temperature of 375°C, a water absorption rate of 0.05%, a dielectric constant of 3.53, and a dielectric loss of 0.0046.

[0070] This embodiment also uses the modified polyphenylene ether for copper clad laminate substrates.

[0071] The preparation method of the copper clad laminate is as follows: 45g of the above-mentioned propidium-modified polyphenylene ether, 50g of FR4 epoxy resin and 0.5g of resin curing agent for copper foil substrate are placed in 50mL of butanone, stirred and dissolved at room temperature, coated with 0.25mm, dried at 100 degrees, placed in a vacuum drying oven at 170 degrees for curing for 3 hours, cooled and demolded to obtain a 25um thick dry film, and then the dry film and copper foil are hot-pressed to obtain a copper clad laminate.

[0072] The water absorption rate, dielectric constant and dielectric loss of the obtained copper clad laminate were tested, and the test results showed that the water absorption rate of the copper clad laminate was 0.36%, the dielectric constant was 3.56, and the dielectric loss was 0.0048.

[0073] The above embodiments are preferred implementation modes of the present invention and are only used to facilitate the description of the present invention. They are not intended to limit the present invention in any form. Any person with ordinary knowledge in the relevant technical field, if they do not depart from the scope of the technical features of the present invention, can make equivalent embodiments by partial changes or modifications to the technical contents disclosed in the present invention, and they still fall within the scope of the technical features of the present invention without departing from the technical features of the present invention.

Claims

1. An aziridine-modified polyphenylene ether resin, characterized in that: The terminal end group of the polymer main chain is an aziridine strained ring structure; The chemical structure of the aziridine-modified polyphenylene ether is as follows: ; Wherein, R represents a methyl group or a hydrogen atom; n is an independent integer related to the number average molecular weight of the polyphenylene ether; the number average molecular weight of the polyphenylene ether is 1000-6000, and the corresponding n is 8-50; A method for preparing a polyphenylene ether resin, the method comprising the following steps: (1) polyphenylene ether is dissolved in an anhydrous solvent, an acid dressing is added, acryloyl chloride is added dropwise at 0-5°C, and after the addition is completed, the mixture is returned to room temperature and stirred for 8-12 hours; after the reaction is completed, the solvent is removed by vacuum distillation, triethylamine hydrochloride or pyridine hydrochloride by-products are removed by washing with water, and the mixture is precipitated in a mixed solvent of methanol and water, and then solid-liquid separation is performed, and finally dried in a vacuum environment at 40°C to obtain a modified polyphenylene ether having an acrylate functional group as the terminal group; The anhydrous solvent is tetrahydrofuran or dichloromethane; the acid coating agent is any one of triethylamine, pyridine and diisopropylethylamine; the molar ratio of the polyphenylene ether, acryloyl chloride and the acid coating agent is 1:4-8:2-6; (2) Adding an excess of aziridine to a modified polyphenylene ether having an acrylate functional group as the terminal group in an anhydrous solvent, stirring at room temperature for 15-20 hours, and draining the solvent to obtain an aziridine-modified polyphenylene ether resin; the anhydrous solvent is tetrahydrofuran or dichloromethane; and the molar ratio of the modified polyphenylene ether to aziridine is 1:5-10.

2. Use of an aziridine-modified polyphenylene ether resin according to claim 1 in the preparation of copper-clad laminates.

3. The use of the aziridine-modified polyphenylene ether resin in the preparation of copper-clad laminates according to claim 2, characterized in that: The aziridine modified polyphenylene ether is mixed with one or more of epoxy resin, hydrocarbon resin or cyanate resin, and the copper clad laminate is obtained after curing.

Citation Information

Patent Citations

  • Crosslinkable polyphenyl ether resin, preparation method and use thereof

    CN103102484B

  • Preparation method of vinylbenzyl-polyphenyl ether composition

    CN104072751A

  • An organosilicon-modified polyphenylene ether resin, its preparation method and uses

    CN106916293B

  • Resin composition and use thereof

    CN102993683A

  • N-alkylaziridine prepolymers as a dental material

    US20040149164A1